US Basel III Final Rule on banks’ capital requirements: A different-size-fits-all approach - Masera, Rainer (PSL Quarterly Review, 2014)
The US Basel III Final Rule was issued by the Banking Agencies (Fed, OCC and FDIC) in July 2013. The Rule implements the international Basel III framework defined by the Basel Committee on Banking Supervision and represents a major overhaul of the US banks’ capital requirements, since the adoption of Basel I in 1992. The Rule incorporates provisions contained in the Dodd-Frank Act (2010). The purpose of this note is to highlight some key specific features of the US standard. In particular, it is argued that the US Rule introduces, de facto, a modular approach according to size and complexity and places great emphasis on leverage requirements for systemic banks, to avoid a mere backstop character of the non-risk-based capital ratios. These two features stand in contrast with the EU transposition of Basel III (CRR/CADIV). JEL codes: G21, G28